Thermodynamics - Klein, Sanford A., 1950-; Nellis, Gregory (New York : Cambridge University Press, 2012)
'The objective of this comprehensive text is to provide engineers with the concepts, tools, and experience needed to solve practical real-world energy problems using modern computing tools'--
'This book differs from other thermodynamics texts in its objective which is to provide engineers with the concepts, tools, and experience needed to solve practical real-world energy problems. The presentation integrates computer tools (e.g., EES) with thermodynamic concepts to allow engineering students and practicing engineers to solve problems they would otherwise not be able to solve. The use of examples, solved and explained in detail, and supported with property diagrams that are drawn to scale, is ubiquitous in this textbook. The examples are not trivial, drill problems, but rather complex and timely real world problems that are of interest by themselves. As with the presentation, the solutions to these examples are complete and do not skip steps. Similarly the book includes numerous end of chapter problems, both typeset and online. Most of these problems are more detailed than those found in other thermodynamics textbooks. The supplements include complete solutions to all exercises, lecture slides, software downloads, and additional content on selected topics'--
Machine generated contents note: 1. Basic concepts; 2. Thermodynamic properties; 3. Energy and energy transport; 4. General application of the first law; 5. The second law of thermodynamics; 6. Entropy; 7. Exergy; 8. Power cycles; 9. Refrigeration and heat pump cycles; 10. Property relations for pure fluids; 11. Mixtures and multi-component phase equilibrium; 12. Psychometrics; 13. Combustion; 14. Chemical equilibrium; 15. Statistical thermodynamics; 16. Compressible flow.
Includes bibliographical references and index.
Keywords: Thermodynamics; Engineering -- Problems, exercises, etc